PEMBELAJARAN FLIPPED CLASSROOM BERPENDEKATAN MATEMATIKA REALISTIK UNTUK MENDUKUNG LITERASI MATEMATIS SISWA - Rezky Agung Herutomo; Masrianingsih _ (Universitas Muhammadiyah Semarang, 2021)
This study aims to determine the effectiveness of flipped classroom learning with a realistic mathematics approach to promote students' mathematical literacy. This research was a quasi-experimental study using posttest only non-equivalent control group design. The population of this research was all students of 10th grade in one of public senior higher school in Kendari, Indonesia. Two classes were chosen by purposive sampling as the samples of this study that is X-MIPA 1 as the experimental class and X-MIPA 2 as the control class. The instruments used in this study were a mathematical literacy test. The results of this study show that the flipped classroom learning with a realistic mathematics approach is effective to promote the achievement of students' mathematical literacy.